Application of new materials at converting ship and aviation gas-turbine engines GTE in stationary gas-turbine installations GTI - Романов, В.В.; Коваль, В.А. (Eastern-European Journal of Enterprise Technologies, 2010)
Habits of application of various alloys for the basic units and details stationary GTE, formed on the basis of ship are observed. Results of the comparative analysis of designs of compressors of low and tall pressures GTE DN80, and also the data describing of strength properties of serial materials are resulted. Last achievements in the field of creation of hightemperature alloys aviation GTE are shown.